2015
DOI: 10.1007/978-3-319-27048-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Design-Based Research

Abstract: Abstract. Design-Based Research (DBR) is a relatively new intervention method investigating educational designs applied to real-life settings, and with a dual purpose to develop domain theories and to develop the design, iteratively. This paper is an integrative review, which draws on literature and empirical projects to identify and discuss critical elements in DBR, in particular when doing research in online educational projects, where the learning process expands from a traditional classroom to everyday wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 23 publications
(40 reference statements)
0
8
0
1
Order By: Relevance
“…We used workshops as a method to enhance the participants’ own interests relevant to the domain in question while producing empirical data. 24 Throughout the workshop, we used dialogue tools from The Family Toolbox 25 to facilitate peer-to-peer dialogue. The exercises included storytelling about time of diagnosis, drawing a line on the floor and asking participants to place themselves on the line to indicate how much space diabetes takes up space in everyday life and selecting picture cards/quotes to describe experiences with different types of support.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used workshops as a method to enhance the participants’ own interests relevant to the domain in question while producing empirical data. 24 Throughout the workshop, we used dialogue tools from The Family Toolbox 25 to facilitate peer-to-peer dialogue. The exercises included storytelling about time of diagnosis, drawing a line on the floor and asking participants to place themselves on the line to indicate how much space diabetes takes up space in everyday life and selecting picture cards/quotes to describe experiences with different types of support.…”
Section: Methodsmentioning
confidence: 99%
“…16 Psychosocially, associating positively with peers is important and seems to influence the decision-making process in selfmanagement, distress, negative moods, and negative self-image/confidence-all of which are factors that affect poor glycemic control. 11,17,18 One quantitative study revealed how the age group of emerging adults (18)(19)(20)(21)(22)(23)(24)(25) rated themselves as having the lowest Health-Related Quality of Life (HRQOL) compared to other age groups. 19 This was confirmed by Fischer et al 20 who looked at adolescents and young adults aged 7-27, showing how increasing age is a significant determinant of low rates of HRQOL and low ratings of HRQOL correlated with poorly regulated blood glucose.…”
Section: Introductionmentioning
confidence: 99%
“…In a first phase, the methodological approach aimed to gain insight into the market needs by identifying the real estate sustainability challenges and opportunities. Based on the literature review synthesis and the market studies, a preliminary version of the "Real Estate Lifecycle Meta Benchmark" was proposed [41]. The result of this phase was the definition and validation of the feasibility study requirements; the market needs for a now-called Real Estate Life Cycle Meta Instrument.…”
Section: Developed and Applied Research Designmentioning
confidence: 99%
“…One of the most meaningful approaches to adopt in order to develop an online learning platform that meets the needs and expectations of the target learners, is the Design Based Research (DBR) methodology [7,27]. DBR is explained by Ørngreen [28] as follows:…”
Section: Developing Online Learning Platforms In Design Thinking Educ...mentioning
confidence: 99%